Managing the potential risks of using bacteria-laden water in mineral processing to protect freshwater - Liu, W.; Moran, Chris; Vink, S. (American Chemical Society, 2013)
The minerals industry is being driven to access multiple water sources and increase water reuse to minimize freshwater withdrawal. Bacteria-laden water, such as treated effluent, has been increasingly used as an alternative to freshwater for mineral processing, in particular flotation, where conditions are favorable for bacterial growth. However, the risk posed by bacteria to flotation efficiency is poorly understood. This could be a barrier to the ongoing use of this water source. This study tested the potential of a previously published risk-based approach as a management tool to both assist mine sites in quantifying the risk from bacteria, and finding system-wide cost-effective solutions for risk mitigation. The result shows that the solution of adjusting the flotation chemical regime could only partly control the risk. The second solution of using tailings as an absorbent was shown to be effective in the laboratory in reducing bacterial concentration and thus removing the threat to flotation recovery. The best solution is likely to combine internal and external approaches, that is, inside and outside processing plants. Findings in this study contribute possible methods applicable to managing the risk from water-borne bacteria to plant operations that choose to use bacteria-containing water, when attempting to minimize freshwater use, and avoiding the undesirable consequences of increasing its use. © 2013 American Chemical Society.